Penurunan Derajat Stres Pegawai Di Lembaga “X” Bandung melalui Pelatihan Coping Resources - Yuliana Yuliana; Irene Prameswari Edwina; Lie Fun Fun (Humanitas (Jurnal Psikologi), 2018)
This research was part of the thesis research and was conducted to find out whether the training of coping resources can reduce the stress level on the employees at organization “X” Bandung. The method used in this research is quasi experimental method with design used in this research is one group design, pre-test and post-test design. Validity test on stress and coping resources questionnaire using construct validity with range of r or rs value for stress questionnaire is 0.418 – 0.874 and for coping resources questionnaire is 0.439 – 0.828 and p-value range for stress questionnaire is 0.000 – 0.047 and for coping resources questionnaire is 0.000 – 0.036. Reliability test on stress and coping resources questionnaire using the formula coefficient reliability alpha cronbach with a value of 0.954 for stress questionnaire and 0.943 for coping resources questionnaire. Based on the results of research shows that training coping resources can reduce the stress level on the employees at Organization “X” Bandung. Keywords: coping resources, stress, and training